Surviving Sepsis Campaign: Research Opportunities for Infection and Blood Purification Therapies. (7th September 2021) - Martin-Loeches, Ignacio; Nunnally, Mark E.; Hellman, Judith; Lat, Ishaq; Martin, Greg S.; Jog, Sameer; Kesecioglu, Jozef; De Backer, Daniel; Coopersmith, Craig M.
Abstract : OBJECTIVES: Patients with infection can develop sepsis, and their mortality can be high. An important aspect in the treatment of sepsis is adequate management of the infection. DATA SOURCES: Using a modified Delphi approach, the Surviving Sepsis Campaign research committee recently published a series of 26 priorities for sepsis and septic shock. STUDY SELECTION: Task force members with specific expertise were tasked with generating expanded reviews for all infection questions and a subset of adjunctive therapy questions from the larger list of sepsis priorities. Each question was addressed by one of the six task force members. DATA EXTRACTION: In-depth reviews were then edited by the group as a whole, with added input from the committee cochairs. DATA SYNTHESIS: Six questions were addressed: 1) should empiric antibiotic combination therapy be used in sepsis or septic shock? 2) does optimization of antimicrobial pharmacokinetics and pharmacodynamics impact patient outcomes in sepsis? 3) should viral reactivation resulting from sepsis-induced immunosuppression be treated with antiviral therapy in critically ill septic patients? 4) should rapid diagnostic tests be implemented in clinical practice? 5) what is the role of lung-protective ventilation in sepsis patients without acute respiratory distress syndrome? and 6) how do we determine the efficacy of "blood purification" therapies such as endotoxin absorbers, cytokine absorbers, and plasmapheresis. CONCLUSIONS: The research committee members for the Surviving Sepsis Campaign aimed to explore research questions in order to provide existing evidence and highlight areas of uncertainty and future directions.